Pengaruh Waktu Kontak dan Kecepatan Pengadukan Terhadap Penyerapan Ion Logam Pb2+ Menggunakan Biosorben Kulit Buah Naga Merah (Hylocereus polyrhizus) - Fitri, Nur; Kurniawati, Desy (Departemen Kimia FMIPA UNP, 2023)
The Pb2+ ion is the most common and highly toxic metal ion that can be found in industrial waste. if it enters a water body, it will be difficult to degrade and easily accumulate in the body of organisms. This study aims to reduce the impact of Pb2+ ion pollution in the waters. The biosorption method was chosen in batches by utilizing plantation waste, namely dragon fruit peel as a biosorbent in the absorption of Pb2+ ions, because it is cheap, safe, and effective. Dragon fruit peel contains lignin and cellulose which contain active groups so that it ispotential to be used as a biosorbent. The result showed that the dragon fruit peel adsorbent was able to absorb Pb 2+ ions at an optimum contact time 70 minutes with a stirring speed of 200 rpm which was analyzed using an atomic absorption with the highest absorption capacity of 32,74 mg/g.